FORMULATION AND EVALUATION OF NIOSOMAL IN SITU GEL OCULAR DELIVERY SYSTEM OF BRIMONIDINE TARTRATE : Pharmaceutical Science-Pharmaceutics - V. SATHYAVATHI; HASANSATHALI, A. ABDUL; R. ILAVARASAN; T.SANGEETHA (International Journal of Life Science and Pharma Research, 2012)
The aim of present study was to develop Brimonidine tartrate niosomalinsitu gels forglaucomatreatment. Poor bioavailability of drugs from ocular dosage form is mainly due to tearproduction, nonproductive absorption, transient residence time, impermeability of cornealepithelium.These problemscan be minimized by the use of niosomal vesicular system.Niosomes were formulated by using different ratios of span series and cholesterol. Span 60 (S/C 2:1) niosomeshad highest entrapment efficiency and showed prolonged drug release. Small unilamellar vesicles were observed and had the size of about 50-100 nm. Insitu gelling of niosomal drops was formulated by using HPMC K 15 M and carbopol 940 to maintain the drug localization for extended period of time. The niosomal formulation was transformed into gel when it instilled into the eye. All the gel formulations exhibited pseudo plasticrheological behavior and slow drug release pattern. Antiglaucoma activity of the prepared gel formulations showed more significant and sustained effect in reducing intra ocular pressure than marketed and niosomal drops. Hence niosomalinsitu gelling may have its potential applications than the conventional ocular therapy and to improve the ocular bioavailability with minimal loss of drug.